BIOTRANSFORMATION OF SULPHONATED AZO DYE DIRECT RED 5B BY MARINOBACTER SP. DR-7- A BIOREMEDIAL ASPECT IN MARINE ENVIRONMENT - SHERTATE R.S.; THORAT P.R. (International Journal of Pharma and Bio Sciences, 2013)
A marine bacterium capable of degrading the textile azo dye Direct Red 5B was isolated from natural environments on nutrient medium containing the high salinity and the dye. It was identified as Marinobacter sp. DR-7 (Accession No. HF558993) on the basis of biochemicals and phylogenetic analysis based on 16s rRNA gene sequence. The decolorization of the azo dye Direct Red 5B in nutrient broth and half strength nutrient broth having 8.0% salt concentration was up to 94.00% and 92.00% respectively in 24 hours. The degradation products formed were analyzed by GC-MS technique and it was found that culture degraded Direct Red 5B to the products having molecular weights 98, 99, 100, 149, 150, 149, 150, 149, 150, 223, 149, 150, 57, 113, 149, 167 and 279.The isolate reduced the COD of the dye up to 70%.